2018
DOI: 10.1002/advs.201700858
|View full text |Cite
|
Sign up to set email alerts
|

11% Organic Photovoltaic Devices Based on PTB7‐Th: PC71BM Photoactive Layers and Irradiation‐Assisted ZnO Electron Transport Layers

Abstract: The enhancement of interfacial charge collection efficiency using buffer layers is a cost‐effective way to improve the performance of organic photovoltaic devices (OPVs) because they are often universally applicable regardless of the active materials. However, the availability of high‐performance buffer materials, which are solution‐processable at low temperature, are limited and they often require burdensome additional surface modifications. Herein, high‐performance ZnO based electron transporting layers (ETL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…It is worth emphasizing that the optimized addition of CsPbI 3 QDs (3 wt %) yields an enhancement in the PCE of 35 % relative to the control device, which is the highest increase reported amongst hybrid ternary devices (Supporting Information, Table S3), and more importantly, the efficiency of 10.84 % obtained with our champion device stands out among the highest for devices based on the light harvesting of a PTB7‐Th:PC 71 BM blend …”
Section: Resultsmentioning
confidence: 68%
“…It is worth emphasizing that the optimized addition of CsPbI 3 QDs (3 wt %) yields an enhancement in the PCE of 35 % relative to the control device, which is the highest increase reported amongst hybrid ternary devices (Supporting Information, Table S3), and more importantly, the efficiency of 10.84 % obtained with our champion device stands out among the highest for devices based on the light harvesting of a PTB7‐Th:PC 71 BM blend …”
Section: Resultsmentioning
confidence: 68%
“…More specifically, the photogenerated electron lifetime under open circuit conditions can be estimated with this technique by monitoring the photovoltage response to asmall sinusoidal modulation of the light intensity.F igure 6a shows the Nyquist plots of the IMVS measurements performed on devices with increasing QD loading, which show as emi-circular arc in the complex plane with as light cardioid shape at high-frequencies (near the origin) that is likely related to the RC-attenuation of the circuit in this frequency range.Onthe basis of the theoretical description of IMVS, [57] the characteristic angular frequency at the critical point of the Nyquist plot (the minimum imaginary component value), as highlighted for each plot in Thedependence of the extracted t rec as afunction of the QD loading is displayed in Figure 6b.A so bserved, the device without QDs shows a t rec of 2.6 ms, similar to that previously reported. [44] Upon the incorporation of QDs, t rec rises significantly,p eaking at 7.1 msf or 3wt%,a nd subsequently decreases with further QD loading.I nterestingly,t he trend observed in t rec correlates quite well with the PCE, matching the optimum performance with the longest lifetime.T his is consistent with reports in other systems where increasing carrier lifetimes have been reported to be associated with an improved PCE. [44] It is important to clarify the nature of the recombination pathway that is monitored with IMVS.T ransient absorption spectroscopy studies performed on various polymer/fullerene blends under open circuit conditions have systematically demonstrated that monomolecular recombination starts quickly after photo-excitation extending to the hundreds of nanoseconds timescale,w hereas the bimolecular recombination of dissociated charges extends over the microsecond timescale.…”
Section: Research Articlesmentioning
confidence: 97%
“…[44] Upon the incorporation of QDs, t rec rises significantly,p eaking at 7.1 msf or 3wt%,a nd subsequently decreases with further QD loading.I nterestingly,t he trend observed in t rec correlates quite well with the PCE, matching the optimum performance with the longest lifetime.T his is consistent with reports in other systems where increasing carrier lifetimes have been reported to be associated with an improved PCE. [44] It is important to clarify the nature of the recombination pathway that is monitored with IMVS.T ransient absorption spectroscopy studies performed on various polymer/fullerene blends under open circuit conditions have systematically demonstrated that monomolecular recombination starts quickly after photo-excitation extending to the hundreds of nanoseconds timescale,w hereas the bimolecular recombination of dissociated charges extends over the microsecond timescale. [58][59][60] This suggests that the t rec extracted from the IMVS data corresponds to the kinetics of bimolecular recombination.…”
Section: Research Articlesmentioning
confidence: 97%
See 2 more Smart Citations